Radar Target Classification Using Neural Network and Median Filter - Matousek, Z.; Kurty, J. (Radioengineering Society, 2001)
The paper deals with Radar Target Classification based on the use of a neural network. A radar signal was acquired from the output of a J frequency band noncoherent radar. We applied the three layer feed forward neural network using the backpropagation learning algorithm. We defined classes of radar targets and designated each of them by its number. Our classification process resulted in the number of a radar target class, which the radar target belongs to.
Keywords: classification of ground radar targets; neural net-work; radar signal processing